The effect of the guided inquiry learning model on the improvement of students’ mathematical problem-solving ability - Benazir Shafa Imani; Pentatito Gunowibowo; Santy Setiawati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
Students’ mathematical problem-solving ability remains relatively low, as reflected in their difficulties in understanding problems, connecting relevant concepts, and evaluating and drawing conclusions from their solutions. This study investigated the effect of the guided inquiry learning model on the improvement of students’ mathematical problem-solving ability. A quasi-experimental method with a pretest-posttest control group design was employed. The population comprised 252 eighth-grade students at SMP Negeri 9 Bandar Lampung. Through purposive sampling, 26 students from class VIII-E were selected as the experimental group, while 28 students from class VIII-C were selected as the control group. Data were collected using a mathematical problem-solving ability test and analyzed using the Mann-Whitney U test. The results showed that students who participated in guided inquiry learning achieved greater improvement in mathematical problem-solving ability than those who participated in conventional learning. These findings demonstrate that the guided inquiry learning model has a significant effect on improving students’ mathematical problem-solving ability.